1989
DOI: 10.1111/j.1365-3016.1989.tb00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal thyroid disease and risk of birth defects in offspring: a population‐based case‐control study

Abstract: We investigated the relationship between maternal thyroid disease and the risk of birth defects in offspring using data from a large population-based, case-control study. Cases included 4904 stillborn and liveborn infants with major anomalies diagnosed in the first year of life and born to residents of metropolitan Atlanta between 1968 and 1980. Controls included 3027 normal babies, frequency-matched to cases by race, hospital of birth and quarter of birth. We compared mothers of cases and controls regarding h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 13 publications
1
31
0
Order By: Relevance
“…Thyroid hormone is a well-known trophic factor for normal lung development and alveolar cell differentiation (DeMello et al 1989). Moreover, maternal hypothyroidism has been associated with an increased risk of a variety of birth defects in offspring (Potter 1980;Khoury et al 1989), but information on its role in CDH is lacking. The exact mechanism of teratogenesis is not known but evidence is accumulating that Nitrofen may interact with the embryonic nuclear receptors for thyroid hormone (Manson 1986).…”
Section: Resultsmentioning
confidence: 99%
“…Thyroid hormone is a well-known trophic factor for normal lung development and alveolar cell differentiation (DeMello et al 1989). Moreover, maternal hypothyroidism has been associated with an increased risk of a variety of birth defects in offspring (Potter 1980;Khoury et al 1989), but information on its role in CDH is lacking. The exact mechanism of teratogenesis is not known but evidence is accumulating that Nitrofen may interact with the embryonic nuclear receptors for thyroid hormone (Manson 1986).…”
Section: Resultsmentioning
confidence: 99%
“…Observational Studies We are aware of only two observational studies (i.e., studies that include a comparison group of noncases) that have examined the association of maternal thyroid dysfunction with CS, and their results are mixed [38,39]. The first case-control study did not observe an increased risk of CS among offspring born to mothers who reported a history of thyroid disease, but the study had limited power (it included 63 CS cases, 4 of whom reported a history of thyroid disease), and exposure assessment occurred up to 15 years after delivery [38].…”
Section: Epidemiologic Evidencementioning
confidence: 99%
“…The first case-control study did not observe an increased risk of CS among offspring born to mothers who reported a history of thyroid disease, but the study had limited power (it included 63 CS cases, 4 of whom reported a history of thyroid disease), and exposure assessment occurred up to 15 years after delivery [38]. The second study was based on the National Birth Defects Prevention Study, a population-based case-control study [39].…”
Section: Epidemiologic Evidencementioning
confidence: 99%
“…(Other variables such as Hispanic ethnic status in the United States [Wilson et al, 1992] or other ethnic variation [Hook and Harlap, 1979], and a history of maternal thyroid problems [Khoury et al, 1989] may reflect other significant predisposing factors [Hook, 1994].) The recognition of clusters in space and/or time is therefore potentially important in providing clues to the existence of environmental influences on the frequency of the disorder.…”
Section: Down's Syndromementioning
confidence: 99%